Oncological outcomes of breast cancer patients after planned IORT boost with low-kV x-rays: results of the TARGIT BQR prospective phase IV trial - Goerdt, Lukas; Pömsl, Janina; Kraus-Tiefenbacher, Uta; Brück, Viktoria; Kaiser, Christina; Keymer, Ralf; Abo-Madyan, Yasser; Fleckenstein, Katharina; Berlit, Sebastian; Tuschy, Benjamin; Sütterlin, Marc; Wenz, Frederik; et al. (Strahlentherapie und Onkologie, 2025)
The TARGIT BQR (boost quality registry) phase IV trial investigates clinical outcomes of breast cancer patients with standard external-beam radiotherapy (EBRT) of the whole breast and intraoperative radiotherapy (IORT) with low-kV x‑rays as an anticipated tumor bed boost in a real-world setting.
Gesehen am 01.09.2025